Use of infochemicals for the management of the banana weevil in Uganda - Tinzaara, William; Gold, C.; Dicke, M.; Huis, A. van; Nankinga, C. (2003)
Infochemicals play an important role in the biology of many insect species. An understanding of their role in plant-herbivore-carnivore interactions can be used in the development of tools for the enhancement of environmentally benign alternatives to synthetic pesticides. This review discusses how chemical information mediates ecological interactions between organisms and the role of infochemicals in integrated pest management. Infochemicals can be used in pest monitoring and in pest control, through mating disruption, mass trapping and to aggregate herbivores at delivery sites for biological control agents. Particular emphasis is placed on the potential of using pheromones and kairomones in the management of the banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae), a pest in plantations of East African highland banana and plantain in most banana-growing regions of the world. Cosmopolites sordidus produces an aggregation pheromone that attracts both males and females. This pheromone has been identified and synthesised and is being recommended as an effective agent in the trapping and control of the weevil. The synergism between banana plant extracts (kairomones) and the synthetic pheromone in attracting C. sordidus should be better exploited. Future research areas that can provide information for the development of an infochemical-based trapping system for the management of C. sordidus are discussed.